Audible Frequency Analysis of Ground Flashes - Sidath Abegunawardana; JAP Bodhika; Sankha Nanayakkara; Upul Sonnadara; Mahendra Fernando; Vernon Cooray (ICLP, 2018)
Abstract—Thunder signatures have been categorized into three types using recorded peak pressure. The variation in fundamental frequency initiated by ground flashes has been studied by using an acoustic spectrum of thunder. Stransformation has used to estimate the dominant frequency variation around the peak pressure. The mean fundamental frequencies of type 3 ground and cloud flashes are 160 Hz and 98 Hz respectively. The mean frequencies of type 2 ground and cloud flashes are 108 Hz and 82 Hz respectively. The mean fundamental frequencies of type 1 ground and cloud flashes are 88 Hz and 123 Hz respectively.
Keywords: Spectrogram; Thunder; Cloud flash; Ground flash